Impact of two different extraction methods on chemical composition and antimicrobial activities of multi-ingredients essential oils and hydrosols - Fatemeh Ghavidel; Mohammad M. Zarshenas; Younes Ghasemi; Ahmad Gholami; Amirhossein Sakhteman; Pouya Faridi (Shiraz University of Medical Sciences, 2018)
Herbal medicinal oils and hydrosols are of most useful preparations in folk Persian medicine. Till now no comprehensive evaluation has been performed on the impact of simultaneous extraction or mixing the extracted products on chemical composition profile of those preparations. Current study chemically assesses the impact of two different extraction methods for essential oils (EO) and hydrosols (separated and mixed) on chemical composition and activity. Samples of Mentha spicata L. (MS), Zataria multiflora Boiss. (ZM), Bunium persicum (Boiss.) B.Fedtsch. (BP) and Trachyspermum ammi (L.) Sprague (TA) were subjected to hydrodistillation, either individually or in combination with each other. Hydrosols and EO samples of each plant were mixed to prepared new hydrosol and poly-EO samples mixtures. All samples were injected to GC/MS for analysis. Moreover, anti-microbial activity of EOs and hydrosols were measured by MIC method. ATR-IR spectroscopies were used for recorded finger print from EOs. Carvone, Thymol, Cuminic aldehyde, Thymol were identified as the major constituents of MS, ZM, BP, TA EO samples, respectively. Hydrosol of MS, ZM, BP, and TA revealed to have Piperitenone, Carvacrol, Cuminol and Thymol as main components, respectively. The mixed oil samples, from first part had γ-Terpinene and Carvacrol as major components and hydrosol samples had Thymol as major component, respectively. In mixed oils and hydrosols the major components were γ-Terpinene and Thymol in respective order. This study showed that there were differences between main components, antimicrobial activity, antioxidant and ATR-IR spectroscopy of mixed samples in both preparation methods.